Developing Merdeka Belajar Kampus Merdeka (MBKM) Course Package to Foster Entrepreneurship Among Pre-Service Chemistry Teachers - Sulastri, Sulastri; Nazar, Muhammad; Ichwana, Ichwana (Program Magister Teknologi Pendidikan Universitas Jambi, 2024)
This research aims to develop a Independent Campus Learning Program -Merdeka Belajar Kampus Merdeka (MBKM) course package designed to foster the entrepreneurial spirit among pre-service chemistry teachers in the Chemistry Education Study Program at FKIP Universitas Syiah Kuala. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study conducts a comprehensive needs analysis, designs a curriculum prototype, validates and tests the course package, and evaluates its effectiveness. The results indicate that the developed course package successfully integrates chemistry knowledge with entrepreneurial skills, providing students with practical experience in applying chemistry to develop innovative products based on local resources. Program evaluation also reveals a significant increase in students' insights, entrepreneurial skills, and soft skills, along with a heightened interest in entrepreneurship. This research contributes to the development of a more relevant and applicable curriculum in preparing prospective chemistry teachers with entrepreneurial competencies, aligned with the objectives of the MBKM program